INCIDENCE OF MALIGNANT NEW GROWTHS OF THE POPULATION IN UFA CITY DISTRICT FOR 2012 - L. N. Kudryashova; R. Z. Sultanov (Креативная хирургия и онкология)
In this  work  the  statistical analysis  of  incidence  and  mortality  from  malignant new growths of  the  population of  Ufa  in 2012 is submitted. Dynamics  of  the  main indicators on oncological  incidence  for  3 years is reflected and  comparison since 2002  is given, the structure and  the  gender and  age  analysis  of  malignant new  growths are  presented  in detail.  The index of  accumulation of  the  contingent, indicators of  relative  mortality  and year lethality are calculated.